2012
DOI: 10.5653/cerm.2012.39.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electromagnetic field exposure on the reproductive system

Abstract: The safety of human exposure to an ever-increasing number and diversity of electromagnetic field (EMF) sources both at work and at home has become a public health issue. To date, many in vivo and in vitro studies have revealed that EMF exposure can alter cellular homeostasis, endocrine function, reproductive function, and fetal development in animal systems. Reproductive parameters reported to be altered by EMF exposure include male germ cell death, the estrous cycle, reproductive endocrine hormones, reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 65 publications
(72 reference statements)
0
76
1
8
Order By: Relevance
“…Various studies demonstrated potential adverse effects of EMR in brain (El-Swefy et al, 2008;Ongel et al, 2009), kidney (Kiiatkin et al, 2005;Al-Glaib et al, 2008) and testes (Gye and Park, 2008;Almašiová et al, 2014). In our study, significant structural changes were not apparent in rat liver.…”
Section: Discussionmentioning
confidence: 96%
“…Various studies demonstrated potential adverse effects of EMR in brain (El-Swefy et al, 2008;Ongel et al, 2009), kidney (Kiiatkin et al, 2005;Al-Glaib et al, 2008) and testes (Gye and Park, 2008;Almašiová et al, 2014). In our study, significant structural changes were not apparent in rat liver.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, however, other studies have reported that EMF has no effect on male fertility or else that the effect of EMF depends on intensity, length of exposure, wavelength and distance from EMF (Margonato et al 1995, Cecconi et al 2000, Dasdag et al 2003, Kim et al 2006, Çelik et al 2012, Gye and Park 2012.…”
Section: Discussionmentioning
confidence: 78%
“…A plausible mechanism at the intracellular and intercellular level, for instance, is an interaction via the formation of free radicals or oxidative and nitrosative stress (230)(231)(232)(233)(234)(235)(236)(237)(238). It has been shown in many reports reviewed by Georgiu (15) that reactive oxygen species (ROS) may be involved in radical pair reactions; thus, radical pairs may be considered as one of the mechanisms of transduction able to initiate EMF-induced oxidative stress.…”
Section: Possible Mechanism Of Ehsmentioning
confidence: 99%